2020
DOI: 10.3846/transport.2020.12751
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Heavy Metal Pollutants Emitted by Railway Transport

Abstract: Recently, concern for a rapid increase in heavy metal pollutants released by railway transport has been expressed. Most of pollutant emissions from combustion processes are related to fuel consumption in the internal combustion engines of traction rolling stock. The main pollutants released into the environment cover particulate matter, volatile non-methane organic compounds, sulphur dioxide and nitrogen oxides. In this way, it is likely that the biggest polluters of the environment are traction un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…It can be expected that the increased level of lead in samples taken 5 and 10 m from the tracks may be the result of the impact of road transport, as shown in the studies by Liu et al [40]. Similar observations were made by Vaišk ūnait ė and Jasi ūnien ė [15], who found that the highest concentrations of Pb and Cd were recorded at a distance of 5.0 m from railroad sleepers in the upper (up to 10 cm) layer of soil.…”
Section: Railroad Areas In Tarnowskie Górysupporting
confidence: 69%
See 1 more Smart Citation
“…It can be expected that the increased level of lead in samples taken 5 and 10 m from the tracks may be the result of the impact of road transport, as shown in the studies by Liu et al [40]. Similar observations were made by Vaišk ūnait ė and Jasi ūnien ė [15], who found that the highest concentrations of Pb and Cd were recorded at a distance of 5.0 m from railroad sleepers in the upper (up to 10 cm) layer of soil.…”
Section: Railroad Areas In Tarnowskie Górysupporting
confidence: 69%
“…Scientists are increasingly paying more attention to the source of many contaminants from the railway. The PHEs can be connected with, i.e., abrasion of wheels and rails or even with the materials that conserve railway sleepers [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that the coal or crude oil used for household heating, gasoline, and diesel vehicle exhaust is of the major problems in urban soil pollution [29]. Concluding, the contamination seems to be significantly increasing near the commercial port of the city of Volos, close to the railway station, and in the intercity bus station along with the big and heaviest traffic roads of Volos [62]. The present study could give rise to further and more thorough research in the future.…”
Section: Maps Of Geo-accumulation Indexmentioning
confidence: 99%
“…As for the Pb, Zn, and Cd found in the #S1 area, an important source of contamination is the train station. Scientific literature reveals that friction processes between wheelsets and rails during rail transport cause railways to release heavy metals including Zn, Cd, and Pb into the environment [ 29 , 30 ]. The industrial area (#S2–#S3) is characterized by industries of different types.…”
Section: Discussionmentioning
confidence: 99%